Somatic Copy Number Amplification and Hyperactivating Somatic Mutations of EZH2 Correlate With DNA Methylation and Drive Epigenetic Silencing of Genes Involved in Tumor Suppression and Immune Responses in Melanoma - Jessamy Tiffen (Neoplasia: An International Journal for Oncology Research, 2016)
The epigenetic modifier EZH2 is in the center of a repressive complex controlling differentiation of normal cells. In cancer EZH2 has been implicated in silencing tumor suppressor genes. Its role in melanoma as well as target genes affected by EZH2 are poorly understood. In view of this we have used an integrated systems biology approach to analyze 471 cases of skin cutaneous melanoma (SKCM) in The Cancer Genome Atlas (TCGA) for mutations and amplifications of EZH2. Identified changes in target genes were validated by interrogation of microarray data from melanoma cells treated with the EZH2 inhibitor GSK126. We found that EZH2 activation by mutations, gene amplification and increased transcription occurred in about 20% of the cohort. These alterations were associated with significant hypermethylation of DNA and significant downregulation of 11% of transcripts in patient RNASeq data. GSK126 treatment of melanoma lines containing EZH2 activation reversed such transcriptional repression in 98 candidate target genes. Gene enrichment analysis revealed genes associated with tumor suppression, cell differentiation, cell cycle inhibition and repression of metastases as well as antigen processing and presentation pathways. The identified changes in EZH2 were associated with an adverse prognosis in the TCGA dataset. These results suggest that inhibiting of EZH2 is a promising therapeutic avenue for a substantial fraction of melanoma patients.